Coats’ Disease: A Comprehensive Review of Its Pathophysiology, Diagnosis, and Advances in Treatment - Ucgul, Ahmet Yucel; Özdek, Şengül (Seminars in ophthalmology, 2025)
Coats' disease, first described by George Coats in 1908, is a rare ocular disorder primarily affecting young males, often unilaterally. It is characterized by retinal telangiectasia, aneurysms, and exudation, which, in severe cases, can lead to blindness, painful red eye, or ocular atrophy, particularly with early childhood onset. Over the last century, advancements have been made in understanding its natural history, morphology, incidence, and clinical manifestations, showing a male predominance without significant ethnic disparities. This review aims to provide a comprehensive overview of Coats' disease, focusing on its pathogenesis, clinical presentation, diagnostic methods, and management strategies. The pathogenesis of Coats' Disease is multifactorial, involving inflammatory, vascular, and potentially genetic components. Early theories suggested inflammation as the primary cause, but modern research highlights the role of vascular endothelial growth factor (VEGF), where ischemic retinal areas elevate VEGF levels, promoting angiogenesis and impairing the blood-retinal barrier. Clinically, the disease is asymptomatic in early stages but progresses to symptoms like reduced visual acuity, strabismus, and leukocoria, typically within the first decade of life. Diagnostic methods include fundus fluorescein angiography, optical coherence tomography (OCT), and OCT angiography (OCTA), with recent studies identifying reduced blood flow density in capillary networks. Management ranges from intravitreal anti-VEGF agents and steroids to surgical options like pars plana vitrectomy and transscleral drainage, with additional techniques such as laser photocoagulation and cryotherapy proving effective in advanced stages. The prognosis of Coats' Disease heavily depends on the stage of disease at presentation. Early detection and intervention can preserve vision, but advanced stages often result in poor outcomes. Factors such as younger age at presentation, advanced stage, and severe manifestations are associated with more aggressive progression and poorer prognosis. This review highlights the importance of early diagnosis and a multifaceted management approach, emphasizing the need for further research into its pathophysiology and innovative treatment strategies to improve patient outcomes.